Effect of remineralizing gels on microhardness, color and wear susceptibility of bleached enamel - Crastechini, Erica [UNESP]; Bühler Borges, Alessandra [UNESP]; Gomes Torres, Carlos Rocha [UNESP] (Operative Dentistry, 2019)
Objectives: To evaluate the effect of a remineralizing gel combining fluoride and calcium silicate/phosphate or a sodium fluoride gel on bleached enamel microhardness, color, and wear susceptibility. Methods and Materials: Two hundred forty bovine enamel-dentin samples were prepared. Baseline analysis of Knoop microhardness, col- or coordinates (L*a*b*), and surface profile were performed. According to the baseline microhardness values, specimens were stratified into six groups (n=40): NC (negative control)—no treatment; BL (positive control)—bleaching with 40% hydrogen peroxide gel (Opalescence Boost, Ultradent); BL/Rs—bleaching + application of calcium silicate/phosphate gel (Regenerate Serum, Unilever - Rs); Rs/BL—Rs + bleaching; Rs/BL/Rs—Rs + bleaching + Rs; and BL/F—bleaching + 2% sodium fluoride gel. After the treatment described for each group, color change (DE) and microhardness were evaluated again. To evaluate abrasion susceptibility, samples were randomly divided into two subgroups, according to the toothpaste used (Cp—Close Up or Rt—Regenerate), and underwent 100,000 brushing strokes. The profile of each sample was evaluated and the mean wear calculated. The data were analyzed by ANOVA and Tukey tests. Results: All bleached groups showed a significant reduction of microhardness in relation to the negative control. The groups treated with remineralizing gels showed a significantly higher microhardness and less wear than the positive control, although nonsignificant differences were observed among them. Nonsig-nificant differences in DE were found among bleached groups. The groups brushed with Regenerate toothpaste showed significantly less wear than those brushed with Close Up toothpaste. Conclusions: The remineralizing gels did not interfere with bleaching efficacy. However, all the treatments minimized the surface hardness reduction caused by the bleaching procedure and enamel loss after abrasion. Regenerate toothpaste resulted in less enamel abrasion.